Thermoanalytical and dynamic mechanical analysis of commercial geomembranes used for fluid retention of leaching in sanitary landfills - Valentin, Clever Aparecido; da Silva, Jefferson Lins; Kobelnik, Marcelo; Ribeiro, Clovis Augusto [UNESP] (Springer Nature, 2018)
Studying thermal behavior is very important for monitoring the quality of polymers on an industrial scale. Commercial geomembranes are materials with low permeability that can be used for multiple purposes, such as geotechnical engineering in liners for potable water. They can also be used as liners for waste liquid, e.g., sewage sludge and soil coverings for landfills. In this paper, the mechanical and thermal behavior of four geomembranes with thicknesses around 2.1, 1.9, 1.7 and 0.8 mm, sold in Brazil by different companies, was evaluated. Thickness, density, tension, puncture and tear resistance and carbon black content were used to characterize the properties of these materials. Thermogravimetry, differential thermal analysis, differential scanning calorimetry (DSC) and dynamical mechanical analysis (DMA) were used to examine the evolution of these geomembranes thermal behavior. Moreover, activation energy of the thermal decomposition was estimated from non-isothermal kinetics. The results obtained by thermogravimetry showed that the geomembranes have a different thermal behavior from each other. Data obtained by DSC showed a widening of the melting peak after the second heating. Activation energy values obtained by the Flynn–Wall–Ozawa and Capela–Ribeiro isoconversional methods for each sample showed variations between them. Based on the DMA experiment, the store modulus (E′), loss modulus (E″) and tan δ showed different behaviors for the 0.8-mm sample and no significant changes in the other samples. Concerning the mechanical properties, it can be observed that the density and black carbon data have compatible values between the samples.
Keywords: DMA; Geomembranes; Mechanical texts; TG/DTG